Phytochemical Screening, Determination of Total Phenolic Contents and Total Flavonoid Contents of Pod Purified Extract from Caesalpinia pulcherrima (L.) Sw. - Sovia Lenny; Febriyanti Br Surbakti; Juliati Br Tarigan (Journal of Chemical Natural Resources, 2025)
Caesalpinia pulcherrima (L.) Sw. is traditionally used in medicine and is thought to be influenced by the presence of secondary metabolites, especially phenolic compounds and flavonoids. However, identifying the phytochemical compounds of Caesalpinia pulcherrima (L.) Sw. plants, especially on the pods, are less discussed. Here, we propose research on the identification of secondary metabolite compounds of pod-purified extract from Caesalpinia pulcherrima (L.) Sw. using phytochemical screening and also the determination of total phenolic and total flavonoid content. The extraction of Caesalpinia pulcherrima (L.) Sw. pods were processed by maceration and fractionation methods to obtain the purified extract. Total phenolic contents were determined using the Folin-Ciocalteu method. Meanwhile, total flavonoid contents were determined using the AlCl3 method. The result showed that the purified extract of Caesalpinia pulcherrima (L.) Sw. pods contained phenolics, flavonoids, alkaloids, and saponins. The total phenolic and total flavonoid content in the pod purified extract were 326.038 mg GAE/g extract and 290.026 mg QE/g extract, respectively.